All-XUV pump-probe transient absorption spectroscopy of the structural molecular dynamics of Di-iodomethane - Rebholz, Marc; Ding, Thomas; Despré, Victor; Aufleger, Lennart; Hartmann, Maximilian; Meyer, Kristina; Stooß, Veit; Magunia, Alexander; Wachs, David; Birk, Paul; Mi, Yonghao; Borisova, Gergana; et al. (Physical review. X, Expanding access, 2021)
In this work, we use an extreme-ultraviolet (XUV) free-electron laser (FEL) to resonantly excite the I: 4d5/2-σ∗ transition of a gas-phase di-iodomethane (CH2I2) target. This site-specific excitation generates a 4d core hole located at an iodine site, which leaves the molecule in a well-defined excited state. We subsequently measure the time-dependent absorption change of the molecule with the FEL probe spectrum centered on the same I: 4d resonance. Using ab initio calculations of absorption spectra of a transient isomerization pathway observed in earlier studies, our time-resolved measurements allow us to assign the timescales of the previously reported direct and indirect dissociation pathways. The presented method is thus sensitive to excited-state molecular geometries in a time-resolved manner, following a core-resonant site-specific trigger.